Evaluation of the Performance of the Turkish Regulatory Agency: Recommendations for Improved Patients’ Access to Medicines - Koyuncu, Oguzhan (Front Pharmacol, 2020)
BACKGROUND: This study was to evaluate the Turkish regulatory review process and timelines between 2016 and 2018 with a view to assess the changes that had taken place since the previous study, which evaluated the Turkish review processes and timelines 2013 to 2015. METHODS: Data related to the Turkish Medicines and Medical Devices Agency (TİTCK) organizational structure and general information were collected from publicly available sources. A standard questionnaire was then used to collect data with the aim of identifying the TİTCK’s review practices and key milestones for the marketing authorization process. Subsequently, a comparison with the previous study was conducted to identify the key changes and developments that had taken place from 2015- 2018. RESULTS: The TİTCK has made considerable efforts to improve its regulatory capacity since 2016, which has contributed to the overall decrease in the agency review times. The overall median approval time for new active substances; however, increased from 529 calendar days (2016) to 663 calendar days (2018), with the review time in the agency decreasing from 408 calendar days to 326 calendar days, while the company time increased from 137 to 268 calendar days, respectively, over this period. CONCLUSIONS: For the TİTCK to become an international reference agency, they will need to fully implement good review practices and a structured framework for benefit-risk assessment and decision making; consider implementing verification and abridged reviews based on a reliance model and expedite the PIC/S mutual recognition process as well as become a full member of the International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH).